Strategies for core competence in business support services - Tan, Dexter Jopons P. (Davao City School of Management, University of the Philippines Mindanao, 2006)
The objective of this study is for the Matrix Management Corporation (MMC) to formulate a three-year STRATEGIC PLAN based on a well-studied external environment and a careful appraisal of its internal environment. A three-year timetable for the achievement of the firm's business goals is incorporated in the strategic plan. MMC basically belongs to the business services industry, which includes among others, tax, accounting, auditing, bookkeeping, and consultancy services. It is in the business of providing business support services to the Matrix Group of Companies. The growing complexity of the business operations of MMC's clients coupled with the necessity to increase the quality of services offered at the least possible cost were the basis of the proposed strategies focused on cost-efficiency and capability building. Technology will form a major part of the firm's implementation of strategies, especially in its thrust to develop an enterprise system that will provide real time access to information for decision making. The plan incorporates the standardization of routine services to provide consistency and efficiency in the delivery of services and the development of the quality of human resources to cater to the changing needs of clients. Human resources will be the source of MMC's competitive advantage as the company adapts and thrives in an increasingly challenging business environment. The framework of the Strategy Paper is derived from Tom Koplyay and Jean-Paul Paquin. It was perceived to have the most applicability to the organization. Since the firm's goals are aligned with the over-all goals of the group, the implementation design is given particular attention. The premise of the framework is such that the staffing, structure, incentives offered, and the decision & control components reinforce or dilute each other in the implementation stage of the firm's strategies. The Threats, Opportunities, Weaknesses, and Strengths (TOWS) analysis method was used for environmental assessment and corporate appraisal. Data gathering was done through interviews, brainstorming, and access to websites of agencies and institutions from where some information will be needed. The internal environment assessment was conducted mainly through interviews made with personnel, from the casual employees to the top management, and analysis of employee survey results. The Internal Factor Evaluation Matrix (IFE) and the External Factor Evaluation Matrix (EFE) by David was used to assess the impact of the internal and external environment on the firm. Strategy formulation was facilitated through the use of the Quantitative Strategic Planning Matrix (QSPM), together with the Strategy Analysis Worksheet for services firms developed by Thomas and Lovelock.
Thesis, Graduate(Master in Management)--University of the Philippines Mindanao, 2006
Keywords: Strategic plan